Controlling the dimensionality of charge transport in organic thin-film transistors - Laiho, Ari (National Academy of Sciences, 2011)
Electrolyte-gated organic thin-film transistors (OTFTs) can offer a feasible platform for future flexible, large-area and low-cost electronic applications. These transistors can be divided into two groups on the basis of their operation mechanism: (i) field-effect transistors that switch fast but carry much less current than (ii) the electrochemical transistors which, on the contrary, switch slowly. An attractive approach would be to combine the benefits of the field-effect and the electrochemical transistors into one transistor that would both switch fast and carry high current densities. Here we report the development of a polyelectrolyte-gated OTFT based on conjugated polyelectrolytes, and we demonstrate that the OTFTs can be controllably operated either in the field-effect or the electrochemical regime. Moreover, we show that the extent of electrochemical doping can be restricted to a few monolayers of the conjugated polyelectrolyte film, which allows both high current densities and fast switching speeds at the same time. We propose an operation mechanism based on self-doping of the conjugated polyelectrolyte backbone by its ionic side groups.